Finds of Slavic Pottery from the Site of Podvršje - Glavčine (Archaeologia Adriatica, 2009)
The site of Podvršje-Glavčine is situated in the vicinity of Zadar and it was excavated in several archaeological campaigns from 2002 to 2007 under the leadership of A. Uglešić. During the research an early Christian complex consisting of double basilicae with ancillary rooms and a cemetery was discovered on this position. Besides architectural remains, great number of fragments of stone furniture and architectural decoration was discovered in this complex, as well as fragments of ceramic and glass vessels belonging to Late Antiquity. The entire complex was destroyed in a fire during the first half or middle of the 7th century, as indicated by archaeological finds, and the results of radiocarbon analysis. Among finds which for the most part belong to Late Antiquity, fragments of early medieval ceramic vessels of Slavic technological-typological characteristics found chiefly in the front part of the northern church are particularly interesting. There were six such vessels among which we can distinguish hand made pottery and the one made on slow-turning potter's wheel, as well as undecorated and decorated vessels. Motif of wavy lines between parallel lines is dominant on decorated examples. All vessels are represented by sherds of pots, made of purified clay tempered with calcite grains, and their colour varies depending on the firing process. On the basis of analysis pots can be dated to the second half of the 7th and the first half of the 8th century. It is worth mentioning that these vessels belong to early medieval finds from a settlement which are extremely rare in Dalmatia representing the least explored segment of early medieval pottery production. It is also important to emphasize that these vessels are the only early medieval find at this site. Despite the paucity of these vessels, they represent an exceptionally important testimony of the presence of newly arrived Slavs who used dilapidated early Christian complex at Glavčine as a temporary shelter suitable for a shorter stay.
Keywords: pottery; Podvršje-Glavčine; early Middle Ages; the Slavs